"Superstitious healing remedies" : amulets and talismans in the Spanish Golden Age - Alejandro Junquera Martínez; José Ramón Morala Rodríguez (Études romanes de Brno, 2025)
Based on a selection of words referring to amulets, talismans, and relics obtained from the CorLexIn corpus, we intend to offer a characterisation and description of their morphology and uses, based mainly on lexicographical sources close to the context of the 17th century, which will also allow to analyse their treatment in this context. In addition to the lexicographical work, we propose a document-based analysis using the data provided by the academic corpus, which offers a more general view, as opposed to the vision offered by CorLexIn, which has a more specialised profile and a closer perspective to the linguistic reality of the seventeenth-century period.